PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING PADA TEMA DAERAH TEMPAT TINGGALKU DI KELAS IV SD SWASTA BUDI MURNI 2 TAHUN PEMBELAJARAN2018/2019 - DAKHI, MARTINUS (Jurnal Ilmiah Aquinas, 2019)
Discuss about the area where I live, based on the results of observations done in class IV SD Swasta Budi Murni 2 it was found some problems, they were: has not implement the varian model thus the learning is concerned on that teacher that make students fat unmotivated to study got bored. The problem to the result of students learning. Thus it needs to conduct a classroom action research. Classroom action research consists of four steps namely planning, implementation, observation and reflection which conducted into two cycle with one meeting in every cycle. The subject of this research in students of SD Swasta Budi Murni 2 Class IV in the academic year 2018/2019 with the number of the students are 48. The technique of collecting date use lest and observation.The results of the observation skills of teachers cycle I gained an average percentage score of 70.91% with good criteria. Cycle II obtained the average percentage score 86% with good criteria as well. The data showed an increase in the skills of teachers. The results of the observation activities of students cycle I gained an average of 68 with sufficient criteria. In cycle II, increased with the acquisition of a score of 88 with good criteria. Thoroughly of classical results on prates by 29.17% with an average of 67.5 class, on cycle I Thoroughly of classical learning of 47.91% with an average 73.43 class, and in cycle II Thoroughly of classical learning of 95.83% with an average of 95.45 class. The data showed an increase in student learning results.